KOMUNIKASI MEDIA SOSIAL PERSPEKTIF SOSIOLINGUISTIK: Analisis Kode pada Program Master Chef Junior Indonesia di YouTube - Siti Khodijah; Nina Hayuningtyas (Indonesian Journal of Islamic Communication, 2021)
Online activities which are carried out by people all over the world were massive and intensive. There are many underlying motives and goals of the audience in accessing online services, especially social media. Social media is a communication tool that is used by the users in social process. YouTube is one of it, furthermore, it is one of the biggest platforms where people around the world can share informative videos. In youtube, it is easily to find code switching and code mixing phenomenon. The using of English has entered many fields like politic, economy, education, art and entertainment. There are many radio announcers program mix english in their conversation. Many writers of novels or short stories use some english utterance in their writing. The actrees, actors, politician, economist mix english in their daily conversation. There are also some programs which are adapted from foreign country then applied in Indonesia. In those program, the participants, the judges and also the host mix english into the conversation, and this program can be watched by all of people in YouTube. The main purpose of this study is to analyse the word and phrase that appeared in particular code-mixing data and the factors influencing the code-mixing. This research is descriptive qualitative because the data are in the form of words. From the data analysis, it can be found that From 10 data, the writer found 2 data contained code mixing in phrase, all of them are noun phrases. The rest of it, 8 data, was found by the writer contained Code Mixing in word such as adjective, noun, conjunction. For the factor influences code mixing, the writer found 4 factors. They are low of frequency in 6 data, social value in 3 data, overight in 2 data and pernicious homonymy in 1 datum